Students' Critical Thinking on Argumentative Essay Writing through Cooperative Learning - Romadhoni, Mohammad; Ruqoyyah Amilia Andania; Ai-Chun Yen (Universitas Nahdatul Ulama Surabaya, 2022)
Carried on in non-English major freshman students setting, this study aims to examine how critical thinking skills can be developed through cooperative learning in their argumentative essay writing. An experimental group (n=20) and a control group (n=20) were randomly set up, the students were pre-tested and post-tested to see if there is a significant difference in their assigned essay through the Illinois Critical Thinking Essay Scoring Rubric. The implementation of critical thinking rubrics was carried out by 1) supporting students in cooperation, 2) offering the objective 3) fostering students to develop their ideas in writing. The Paired Sample T-test was used to calculate the difference between the pre-and post-test results. Results confirmed that in the Paired Sample t-test, the mean score (-5000) of the experimental group is statistically higher than the mean of the control group’s (-3900). It indicates that the implementation of the critical thinking strategy effectively develops and promotes students’ critical thinking skills in argumentative essay writing. Through the implementation of five key elements of critical thinking by Sadeghi (2012), students were more open-minded, tolerant, objective, honest and concise, respecting others, and interpreting situations differently. The research offered a different perspective on developing students’ critical thinking strategy use by focusing on longer periods of research and the larger number of participants and also implied the integration of critical thinking scoring rubric and argumentative essay skill performance for future research.